“Ancient Art in American Private Collections” at Harvard - Anonymus, A.
Fig. 1: Lion-Headed Demon (с. 3000 В. С.) — Fig. 2: “Hittite” Fertility Goddess (2000-1500 В. С.) — Fig. 5: Early Persian Alabaster Monkey Drinking. Susa (с. 3000 В. С.) — Fig. 16: Bronze Bull Head. Urartu (9th-8th Century).